Live delivery outcome after tubal sterilization reversal: A population-based study - Malacova, E.; Kemp-Casey, A.; Bremner, A.; Hart, R.; Stewart, Louise; Preen, D. (Elsevier Inc., 2015)
© 2015 American Society for Reproductive Medicine. Objective - To determine the cumulative incidence of live delivery in women who underwent reversal of tubal sterilization. Design - Population-based retrospective cohort study. Setting - Hospitals in Western Australia. Patient(s) - All women aged 20-44 years, with a history of hospital admission for tubal sterilization, who subsequently underwent reversal of sterilization during the period 1985 to 2009 in Western Australia (n = 1,898). Intervention(s) - Data regarding reversal of sterilization and prior tubal sterilization were extracted from routinely collected administrative hospital separation records, until commencement of IVF treatment. Main Outcome Measure(s) - First live-delivery rates. Result(s) - There were 969 first live deliveries observed during the study period. The overall cumulative live-delivery rate was 20% (95% confidence interval [CI] 18-23) within the first year after reversal, 40% (95% CI 38-42) at 2 years, 51% (95% CI 48-53) at 5 years, and 52% (95% CI 50-55) at 10 years. The 5-year cumulative live-delivery rate was significantly lower in women who were aged 40-44 years (26%) compared with younger women (aged 20-29, 30-34, and 35-39 years) (50%, 56%, and 51%, respectively). Conclusion(s) - Women undergoing reversal of sterilization before they reach age 40 years have at least a 50% chance of delivering a live baby within the next 5 years. Up to that age, there is no significant difference in live deliveries. The live-delivery rate halves after the age of 40 years.